Improving Climate Resilience of Federal Road Network in Brazil - World Bank (World Bank, Washington, DC, 2019)
Although Brazil is the fifth largest country in the world, it has a relatively low number of natural hazards. However, its exposure to natural hazards has increased relative to other countries because of insufficient preventive actions in the past, resulting in more damage from natural hazards to both infrastructure and human lives than countries of comparable size would incur. Brazil faces an increasing risk of natural disasters, in particular floods and landslides. The objective of the study is to strengthen capacity of geohazard disaster resilience of federal highway infrastructure in Brazil through reviewing disaster risk management (DRM) capacity for federal road infrastructure and case studies of applying innovative methodologies for assessing disaster risk and evaluating economic benefits of resilience countermeasures. Although floods and landslides are the most recurrent natural disasters in Brazil, this report focuses on the latter, leaving floods for future studies. This report carefully describes how three innovative methodologies that, if properly applied, could improve the effectiveness of landslide risk management, thus reducing economic and human impacts. The report begins with diagnostics of the institutional capacities of geohazard risk management at the federal government level in Brazil. Chapters 1 and 2 include the backgrounds of natural disasters, road systems, and geohazards on roads in Brazil and a review of the road geohazard risk management with overviews of the following areas: institutional capacity and coordination, system planning, engineering designs, operation and maintenance, nonstructural measures, and contingency programming. Then, Chapters 3 and 4 describe the case study of application of the three innovative DRM assessment methodologies. Finally, Chapter 5 shows the suggestions and recommendations for the next steps.